Serum mg, ca, total protein levels in maternal and cord blood and its clinical significance - Tunçer, Müyesser; Yenice, Altay; Özand, Pınar (The Turkish Journal of Pediatrics, 1972)
The maternal and cord blood serum Mg, Ca and total protein levels were determined in 60 normal and 39 pathologic newborns. Placental transfer of these metals, and significant relationships of Ca, total protein levels of infants with pathologic conditions and normal newborns were discussed.It was seen that there was an active placental transfer of Mg and Ca. In all babies, cord blood total protein levels were lower than in the maternal blood. This was especially true in premature infants. Finally it was observed that low Mg levels in maternal and cord blood resulted in babies with hyperbilirubinemia. This last point needs further investigation.